Structures and actors in analyses of political decisions - Christiansen, Peter Munk; Kjær, Anne Mette (Politica. Tidsskrift for politisk videnskab, 2020)
The article identifies some of the most significant developments in the political science literature concerning political decisions in the new millennium. We apply the traditional distinction between structure- and actor-based explanations and find that Danish political science has put a lot of effort into explaining both stability and changes in public policy and political decisions. This has contributed to a better combination of actor- and structure-based explanations; however, gaps in the literature remain. We still have limited knowledge about several elements in political decision making. For example, we lack knowledge about what happens in the early decision-making stage, which in recent years has appeared increasingly closed. Likewise, we have limited knowledge about the role of the bureaucracy in the drafting of political decisions. Finally, there is a lack of qualitative case studies of recent political decisions and therefore a lack of comparative analyses of these decisions. The article calls for research in these areas.